2006
DOI: 10.1159/000097260
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ammonia and Nitric Oxide in the Decrease in Plasma Prolactin Levels in Prehepatic Portal Hypertensive Male Rats

Abstract: Objectives: Since very little is known about neuroendocrine changes that occur in portal-systemic hepatic encephalopathy, we studied plasma prolactin (PRL) levels and the involvement of hyperammonemia, nitric oxide (NO) and dopaminergic and adrenergic systems in the control of this hormone secretion in a male rat model of prehepatic portal hypertension (PH). Methods: We conducted in vivo studies to determine plasma ammonia and PRL levels. Dopamine (DA), dihydroxyphenylacetic acid (DOPAC), epinephrine and norep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Also, the increase in NOS activity and/or content in AP induced NO produc�� tion that directly inhibited PRL secretion from the AP, without the participation of the dopaminergic system. These results demonstrate the alteration of the neuroen�� docrine axis in a model of MHE and opens an interesting area of study that remains largely unexplored [161] .…”
Section: Neuroendocrine Axismentioning
confidence: 63%
See 1 more Smart Citation
“…Also, the increase in NOS activity and/or content in AP induced NO produc�� tion that directly inhibited PRL secretion from the AP, without the participation of the dopaminergic system. These results demonstrate the alteration of the neuroen�� docrine axis in a model of MHE and opens an interesting area of study that remains largely unexplored [161] .…”
Section: Neuroendocrine Axismentioning
confidence: 63%
“…�corticati et al [161] studied plasma prolactin (PRL) levels in our laboratory and the involvement of hyperammone�� mia, nitric oxide (NO) and dopaminergic and adrenergic systems in the control of this hormone secretion in a male rat model of mHE. The authors conducted in vivo studies to determine plasma ammonia and PRL levels, dopamine (DA), dihydroxyphenylacetic acid (DOPAC), epinephrine and norepinephrine content in medial basal hypothalamus (MBH) and anterior pituitary (APs).…”
Section: Neuroendocrine Axismentioning
confidence: 99%
“…It showed that both the globus pallidus and AP could be involved in young CPSS patients. Studies in rats with portosystemic hepatic encephalopathy showed that although plasma catecholamines such as E and NE contents were significantly increased, there was no significant change in hypothalamic-APdopaminergic activity (25).…”
Section: Discussionmentioning
confidence: 96%
“…Other alterations that have been described in this experimental model could also be related to the establishment of a low grade cerebral inflammatory response. These include, for example, an altered blood-brain barrier permeability [ 129 ], neuro-endocrine alterations [ 46 , 130 , 131 ] with a decreased uptake and an increased release of norepinephrine [ 130 ], an upregulation of tyrosin hydroxilase activity [ 132 ], as well as astrogliosis and angiogenesis in the hippocampus [ 133 ]. These functional, biochemical and morphological alterations may possibly help characterize portal hypertensive encephalopathy.…”
Section: Extra-splanchnic Alterations In Portal Hypertensionmentioning
confidence: 99%